Microsatellite markers developed through pyrosequencing allow clonal discrimination in the invasive alga Caulerpa taxifolia - ARNAUD-HAOND, Sophie (2014)
Polymorphic microsatellites were developed for the invasive green algae Caulerpa taxifolia using next generation DNA sequencing. Results showed a limited rate of microsatellites for the amount of sequences, possibly explaining failure of previous attempts for microsatellite development through classical methods. Eight polymorphic loci were selected that exhibited polymorphism and a null or negligible rate of amplification failure. The number of alleles per locus ranged from two to seven. The reconstruction of Multi Locus Genotypes and the heterozygosity and departure from Hardy–Weinberg equilibrium confirmed the influence of clonal reproduction and showed the usefulness of this set of markers to successfully discriminate clonal lineages and analyze the clonal and genetic composition of algal beds. These markers will be used to further investigate the clonal composition and genetic structure in populations of C. taxifolia and to attempt retracing the origin of and pathways followed by invasive clonal lineages.